2015
DOI: 10.1380/ejssnt.2015.129
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of CO Oxidation Catalyzed by Au/TiO<sub>2</sub>: Activity of Small Clusters

Abstract: CO oxidation over a rutile TiO2(110) surface supporting a tetrahedral Au10 cluster has been examined by planewave DFT calculations. O2 adsorbs sideon to the pentacoordinate Ti site of the oxide support with a large energy gain (∼ 2 eV), activated to a peroxide state. O2 adsorption on the cluster is much weaker. The stability and activation state of sideon O2 depends weakly on distance to the cluster. On a Ti site next to the cluster, a sideon O2 reacts with CO adsorbed on the cluster to yield CO2 with a very s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…Concurrently, the occupation of the antibonding orbitals weakens the O–O bond, activating O 2 for CO oxidation. A similar mechanism has been found by the majority of DFT studies,44–46 including ours 47–50. The supported Au clusters thus serve as electron donors to O 2 , as oxygen vacancies do.…”
Section: Co Oxidationsupporting
confidence: 84%
See 1 more Smart Citation
“…Concurrently, the occupation of the antibonding orbitals weakens the O–O bond, activating O 2 for CO oxidation. A similar mechanism has been found by the majority of DFT studies,44–46 including ours 47–50. The supported Au clusters thus serve as electron donors to O 2 , as oxygen vacancies do.…”
Section: Co Oxidationsupporting
confidence: 84%
“…It was found that H 2 O assists O 2 adsorption and activation on Au clusters57 and on Au(111)58 through hydrogen bonding, partial proton sharing, and a surface‐mediated mechanism. We also investigated these effects for two rutile TiO 2 (110)‐supported model clusters: tetrahedral Au 10 and truncated tetrahedral Au 9 48. In the Au 10 model, Ti–O 2 next to the cluster reacted with Au–CO with an activation barrier of 0.13 eV to produce CO 2 and an O adatom.…”
Section: Co Oxidationmentioning
confidence: 99%
“…Although small clusters can change shape to stabilize Ti-OO-Au, our calculation on Au 10 /TiO 2 (110) still finds that Ti-OO-Au is 0.44 eV less stable than Ti−O 2 . 27 In Ti−O 2 (Figure 2a), the O−O bond is not aligned with the Ti 5c row, but is off by 46.5°. The bond is substantially weakened, with a negative charge on O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…O vacancy creation is briefly examined (section ). On the other hand, O 2 on Au-only sites are neglected because they are weakly adsorbed. , Ti 5c sites away from the perimeter have been discussed in our previous studies; , they can also activate O 2 , but adsorption is strongest in the immediate vicinity of the perimeter. The effect of water is not considered here and will be addressed in a future work.…”
Section: Introductionmentioning
confidence: 98%
“…The interface between nanosized Au and the TiO 2 surface is the active site of the catalytic CO oxidation of Au/rutile TiO 2 [1,2,[10][11][12][13][14][15]. A high dispersion of Au is therefore necessary for preparing Au/TiO 2 catalysts, and special techniques, such as the deposition-precipitation method [5], gas-phase grafting [16], solid grinding [17], improved impregnation method including the H 2 reduction process [18][19][20], and using an unusual Au precursor [21] are utilized for the preparation.…”
Section: Introductionmentioning
confidence: 99%